THE WORKS OF MARIA DUCHESS WIRTEMBERSKA: AN EDITORIAL CHALLENGE – WHAT TO PUBLISH, HOW TO PUBLISH, AND WHETHER TO PUBLISH? - Biedrzycka, Marta (Prace Polonistyczne, 2025)
The article explores the possibility of publishing the works of Maria Wirtemberska, the vast majority of which still remain in a manuscript form, and thus making them more available. The issue is considered within the broader context of the (in)visibility of Polish women’s literary contributions in the 19th century. Biedrzycka identifies manuscripts whose editing is advisable and considers whether all the remaining texts by Wirtemberska should be included in a prospective volume. She reflects on the tasks an editor of Wirtemberska’s oeuvre must undertake and the questions they should address, including determining the optimal type of edition. The article examines how Wirtemberska’s works could be published, integrating advancements in technology and contemporary editorial practices. Additionally, it explores the challenges associated with translating the manuscripts.